Comportamiento del consumidor frente al comercio electrónico en la industria de la moda en Medellín (2015)
The way of doing business has evolved over the years and the e-commerce has had a great boom in the world as the new way to contact customers, to source products and services from any store in the world and to meet quickly and reliably the needs and desires of consumers. In Medellin, the fashion industry is a strong sector that requires adapt to the trends of international trade. For that reason, it is very important to understand the behavior of their consumers regarding to e-commerce in order to continue to evolve and attract more customers. The best way to develop this aspect are surveys which show quantitatively the perception of citizens regarding the issue. It is concluded that people from Medellin have adopted the online shopping method but there is still much room for improvement in terms of reliability of stores.